2010
DOI: 10.3846/jcem.2010.45
|View full text |Cite
|
Sign up to set email alerts
|

Thermophysical and Mechanical Properties of Fiber‐reinforced Composite Material Subjected to High Temperatures

Abstract: Abstract. The bulk density, open porosity, matrix density, tensile strength, bending strength, thermal diffusivity, specific heat capacity, thermal conductivity and linear thermal expansion coefficient of high-density glass fiber reinforced cement composite are determined as functions of temperature up to 1000 °C. The basic physical parameters and mechanical parameters are found to exhibit the most important changes between the reference state and 600 °C pre-heating where the increase of porosity is as high as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…Ratio of aggregate in traditional structural concrete is about 85% of concrete volume [6]. Refractory composites are usually formulated as fine grain concrete mixtures with relatively high dose of aluminous cement which is necessary assumption of good resistance to high temperature [7]. Common dose of aluminous cement for refractory composites is about 30% in volume which well document their economical and energy consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Ratio of aggregate in traditional structural concrete is about 85% of concrete volume [6]. Refractory composites are usually formulated as fine grain concrete mixtures with relatively high dose of aluminous cement which is necessary assumption of good resistance to high temperature [7]. Common dose of aluminous cement for refractory composites is about 30% in volume which well document their economical and energy consumption.…”
Section: Introductionmentioning
confidence: 99%
“…These results are more detrimental than other studies conducted previously on the tensile strength of heat-treated UHPFRC specimens. For example, in the study by Vejmelková et al (2010) it was found that high-density glass fibre reinforced cement composite delivers 33% of its nominal tensile strength after heating specimens to 600 ºC [1112 ºF]. The results presented herein suggest that this UHPCFR delivers on average only 36% of its nominal tensile fracture strength after extreme heating treatment.…”
Section: Disc-compact Tension Test (Dct)mentioning
confidence: 39%
“…Studies on fibre addition showed a significant improvement in flexural tensile strength of concrete as well as post-peak tensile softening (ductility) (Barris et al 2012). Other studies investigated the effect of different fibre properties -fibre content, length, material types, spatial orientation, and shape -on concrete performance (Kang et al 2011;Downloaded by [Florida Atlantic University] at 19:10 16 November 2014 Vejmelková et al 2010;Kim et al 2011;Hassan et al 2012;Grinys et al 2013;Pajak et al 2013). The results of these studies have shown that flexural tensile strength of UHPFRC increases linearly with respect to the fibre volume ratio from 0% to 5%, and that strength parameters are also linearly dependent on fibre content (Kang et al 2011).…”
Section: Introductionmentioning
confidence: 97%
“…It was proved that utilization of reinforcement should improve not only tensile strength but also other mechanical properties, its durability, fire resistance, etc. Nowadays, the most usual reinforcement is not just a steel bar, but an application of various kinds of fibres becomes common, such as steel fibres [1], carbon fibres [2], glass fibres [3], or organic fibres. The development of polymers fibres represents another possibility of concrete reinforcement.…”
Section: Introductionmentioning
confidence: 99%
“…This matrix, in the main part of this study, should have been upgraded. Since it was proved in previous studies [2,3,5] that fibres can improve thermal resistance, and para-aramid fibres seem to be suitable reinforcing materials (thanks to their adequate properties [7]), the matrix was reinforced by para-aramid fibres. So the main part of this study deals with residual properties of a para-aramid composite material based on cement compared to the same composite material with no reinforcement.…”
Section: Introductionmentioning
confidence: 99%